Optical trapping and manipulation of a single calix[4] arene microcluster in water - Nur Izzati Mahadi (2022)
This research aimed to optically trap and manipulate a single calix[4]arene microcluster in water. The optically trapped microclusters were evaluated in terms of their optical stiffness and rotatability with respect to the variation of microclusters' effective radius and laser power density. The calixarene microclusters contained solution was prepared by sonicating a vial containing a mixture of 1.7 mg of calix[4]arene powder in 1 ml of deionised water for three minutes. Calix[4]arene microclusters in the effective radius range between 0.5 and 3.5 m were optically trapped using a 976 nm laser at laser power densities between 0.67 and 2.30 MW/cm2 with laser sport size 1.1 m. A quadrant photodiode (QPD) collected the scattered light from a single trapped microcluster. The QPD signal was analysed using a custom-made program named OSCal to determine the corner frequency of the optical trap. A quarter waveplate was introduced to the laser path to change the laser polarisation state and induce microcluster rotation. The rotatability of the trapped microcluster was determined by analysing the QPD signal and particle tracking method. Results showed that as the laser power density increases, the corner frequency of the trapped microcluster also increases. Furthermore, the trapped microcluster rotated faster as the laser power density increased regardless of the microcluster's effective radius. To conclude, calix[4]arene in the form of a microcluster can be optically trapped and respond to the circularly polarised light. The strength of the optical stiffness and the magnitude of the rotatability of a trapped calix[4]arene microcluster depend on the laser power density. This research implies the broadening potential of light-manipulated calix[4]arene as a microprobe or microactuator in a liquid.